DEFOLIATION LEVELS AT VEGETATIVE AND REPRODUCTIVE STAGES OF SOYBEAN CULTIVARS WITH DIFFERENT RELATIVE MATURITY GROUPS - Durli, Murilo Miguel (2020)
Soybean tolerance to defoliation may be affected by relative maturity group (RMG) of the cultivar. For this reason, this study was carried out to evaluate the effects of artificial defoliation at vegetative and reproductive stages on the agronomic performance of soybean cultivars with different RMG. Two experiments were carried out in greenhouse conditions in Lages, Santa Catarina State, Brazil. Defoliation was carried out at V6 in the first experiment and at R3 in the second experiment. Three cultivars with contrasting RMG were used: BMX Veloz (RMG of 5.0, indeterminate growth habit), NA 5909 (RMG of 5.9, indeterminate growth habit), and TMG 7262 (RMG of 6.2, semi-determinate growth habit). Each cultivar was submitted to five defoliation levels: 0.0, 16.6, 33.3, 50.0, and 66.6%. Leaf expansion after defoliation, grain yield and its components were determined. The BMX Veloz showed lower leaf expansion capacity and lower grain yield when compared to the other cultivars when defoliated at V6. Grain yield of the three cultivars only showed significant decreases with defoliation levels higher than 16.6% at R3. The cultivar BMX Veloz is less tolerant to defoliation during the vegetative stage when compared to the cultivars NA 5909 and TMG 7262. Cultivar maturity group does not interfere with soybean tolerance to defoliation at the reproductive stage in greenhouse conditions.